SOME OBSERVATIONS ON THE STATEMENT OF APPLICATION FUNDS. - Dickerson, W. E.; Jones, J. Weldon (The Accounting Review, 1931)
Abstract Doubtless the cash account is one of the oldest of accounts. Business operations have revolved round the cash account from the very beginning of business. It follows that the technique of accounting and the operation of business organizations can hardly hope to get away from so fundamental concept. One cannot expect the statement of cash receipts and cash reimbursements to be displaced even if all businesses were to be placed on the accrual basis of accounting. One might well question the accuracy of the small business man who regards his bank balance as his indicator of profits, but one cannot too quickly criticize his judgments on fundamentals. Perhaps the accrual basis of accounting is partly to blame for the shift of emphasis from the funds involved to the net income produced. At any rate, it seems that we have gone too far in leaving out of the picture the significance of the shift in funds which occurs with business operations. This statement applies almost equally to textbooks on accounting and to the work of auditors and interpretative accountants. That one has failed to appreciate the fact that shift of funds in a business is still of major importance, is evidenced both by the relative newness of the Funds-Provided-and-Their-Application Statement and the lack of its wide use and development.